New records of phytoplankton for Bangladesh. 6. Lepocinclis Perty, Strombomonas Defl., Astasia Dujardin, Menoidium Perty - Khondker, Moniruzzaman; Bhuiyan, Rauf Ahmed; Yeasmin, Jenat; Alam, Munirul; Sack, R. Bradley; Huq, Anwar; Colwell, Rita R. (Bangladesh Journal of Plant Taxonomy, 2008)
The paper deals with a systematic account of 17 euglenoid phytoplakton. Of these, seven taxa belong to Lepocinclis and seven to Strombomonas. The other three taxa are Astasia cylindrical Pringsheim, A. pygmaea Skuja and Menoidium tremulum Skv. The taxa are reported from some pond ecosystems located in Pirojpur and Barisal districts of Bangladesh. Keywords: Phytoplankton, New records, Bangladesh, Lepocinclis, Strombomonas, Astasia, Menoidium, Ponds Â DOI: 10.3329/bjpt.v15i2.1740 Â Bangladesh J. Plant Taxon. 15(2): 107-114, 2008 (December)